Inpatient Admission versus Emergency Department Management of Intussusception in Children: A Systemic Review and Meta-Analysis of Outcomes - Amuddhu, Sanjena Kumar; Chen, Yong; Nah, Shireen Anne (European Journal of Pediatric Surgery, 2019)
Introduction Recent literature advocates outpatient emergency department (ED) management of intussusception citing low recurrence rates and postreduction events after uncomplicated ileocolic reduction. However, few studies include both inpatient and outpatient cohorts. We performed a systematic review and meta-analysis to compare recurrence rates and length of hospital stay between the groups.Materials and Methods Studies published in English up to January 2018 were searched from Medline, Embase, Google Scholar, and Cochrane databases, using a combination of the terms ‘intussusception,’ ‘reduction,’ and ‘management’. A meta-analysis of studies comparing outcomes after successful intussusception reduction in children between inpatients and ED patients was performed.Results No randomized controlled trials (RCT) were found. Nine observational studies (eight retrospective and one prospective) were included, comprising 546 inpatients and 776 ED cases. There was no statistical difference in overall recurrence rate between inpatients (8.8%) and ED (10.1%) (pooled odds ratio [OR] = 1.09; 95% confidence interval [CI] 0.74–1.62; P = 0.66; I2 = 0). Five studies reported early recurrence (<48 hours) with no difference (pooled OR = 1.27; 95% CI 0.46–3.48; P = 0.65; I2 = 0). Five studies reported postdischarge recurrence rate with no difference (pooled OR = 1.57; 95% CI 0.71–3.48; P = 0.27; I2 = 34%). Five studies reported recurrence requiring surgery with no difference (pooled OR = 0.99; 95% CI 0.32–3.06; P = 0.99; I2 = 0). Methods of reduction were air, barium, or other contrast enema.Conclusion Management of intussusception in the ED after uncomplicated reduction appears acceptable. However, evidence levels are low, and RCT should be performed to adequately evaluate the safety of outpatient management of pediatric intussusception.
Keywords: intussusception; inpatient; emergency department; recurrence; children